Platform affordances and political participation: how social media reshape political engagement - Theocharis, Yannis; Boulianne, Shelley; Koc-Michalska, Karolina; Bimber, Bruce (My University, 2022)
Political participation opportunities have been expanding for years, most recently through digital tools. Social media platforms have become well integrated into civic and political participation. Using a cross-national sample from the United States, United Kingdom and France, this article examines whether acts of participation associated with social media should be classified using a traditional, five-factor solution to the structure of participatory acts. The distinction between online and offline participation is set aside, focusing instead on acts supported and enabled by social media, and in particular on differences between the use of Twitter and Facebook. The analysis shows that acts enabled by social media do not load with traditional factors in the structure of participation. Political acts employing Twitter and Facebook are distinct in the factor structure of participation.
Keywords: political participation; social media; platforms; affordances; political engagement